DETERMINAN KEJADIAN TUBERKULOSIS PARU PADA USIA DEWASA DI WILAYAH KERJA PUSKESMAS PARUNGPANJANG KABUPATEN BOGOR TAHUN 2021 - Rifda Nurul Dzakiyah, (2022)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. By 2020, tuberculosis will be the 13th leading cause of death in the world. Indonesia is on the list of 30 countries with the highest TB burden and is the third highest in the world in terms of TB incidence. This study aimed to analyze determinants of pulmonary tuberculosis at Parungpanjang Health Center, Bogor Regency in 2021. This study used a case-control research design with purposive sampling using a sample of 105 respondents. Data analysis used univariate analysis, bivariate analysis with chi square test, and multivariate analysis with multiple logistic regression. The results of multivariate analysis showed that the determinants of pulmonary TB among adults at Puskesmas Parungpanjang were education level variables (OR=3.782; 95% CI=1.281-11.165), smoking status (OR=6.831; 95% CI=2.295-20.331), and close contact with pulmonary TB patients (OR=7,750; 95% CI=2,267-26,497). The recommended for Parungpanjang Health Center is increasing TB surveillance both in terms of case detection and close contacts as well as risk factors. In addition, it is also recommended for improve health promotion to the community about TB.